Landlockedness, Infrastructure And Trade : New Estimates For Central Asian Countries - Grigoriou, Christopher (The World Bank, 2007)
This paper assesses the impact of internal infrastructure and landlockedness on Central Asian trade using a panel gravity equation estimated on a large sample of countries (167 countries over 1992-2004). The panel structure of the dataset makes it possible to control for country-pair specific effects (as opposed to the usual importer and exporter effects) that would otherwise be captured by the coefficients of time-invariant variables such as distance or landlockness. Our findings highlight the need to pursue a dual policy agenda. First, transit corridors are regional public goods and should be managed as such through international cooperation. International Financial Institutions can -and do- play a key role in this regard through assistance, coordination and policy dialogue. Second, the Central Asian countries should actively seek diversification of their transit corridors to prevent the creation or maintenance of monopoly positions in transit and bottleneck points such as trans-shipment platforms